Adverse Event Profile During the Treatment of Helicobacter pylori: A Real-World Experience of 22, 000 Patients From the European Registry on H. pylori Management (Hp-EuReg). (8th June 2021) - Nyssen, Olga P.; Perez-Aisa, Angeles; Tepes, Bojan; Castro-Fernandez, Manuel; Kupcinskas, Juozas; Jonaitis, Laimas; Bujanda, Luis; Lucendo, Alfredo; Jurecic, Natasa Brglez; Perez-Lasala, Jorge; Shvets, Oleg; Fadeenko, Galina; et al.
Abstract : INTRODUCTION: The safety of Helicobacter pylori eradication treatments and to what extent adverse events (AEs) influence therapeutic compliance in clinical practice are hardly known. Our aim was to assess the frequency, type, intensity, and duration of AEs, and their impact on compliance, for the most frequently used treatments in the "European Registry on Helicobacter pylori management." METHODS: Systematic prospective noninterventional registry of the clinical practice of European gastroenterologists (27 countries, 300 investigators) on the management of H. pylori infection in routine clinical practice. All prescribed eradication treatments and their corresponding safety profile were recorded. AEs were classified depending on the intensity of symptoms as mild/moderate/severe and as serious AEs. All data were subject to quality control. RESULTS: The different treatments prescribed to 22, 492 patients caused at least 1 AE in 23% of the cases; the classic bismuth-based quadruple therapy was the worst tolerated (37% of AEs). Taste disturbance (7%), diarrhea (7%), nausea (6%), and abdominal pain (3%) were the most frequent AEs. The majority of AEs were mild (57%), 6% were severe, and only 0.08% were serious, with an average duration of 7 days. The treatment compliance rate was 97%. Only 1.3% of the patients discontinued treatment due to AEs. Longer treatment durations were significantly associated with a higher incidence of AEs in standard triple, concomitant, bismuth quadruple, and levofloxacin triple or quadruple therapies. DISCUSSION: Helicobacter pylori eradication treatment frequently induces AEs, although they are usually mild and of limited duration. Their appearance does not interfere significantly with treatment compliance.